2020
DOI: 10.1016/j.chest.2020.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Variation Between Multidisciplinary Tumor Boards in Clinical Staging and Treatment Recommendations for Patients With Locally Advanced Non-small Cell Lung Cancer

Abstract: on behalf of the MDT Study Group * BACKGROUND: Accurate diagnosis and staging are crucial to ensure uniform allocation to the optimal treatment methods for non-small cell lung cancer (NSCLC) patients, but may differ among multidisciplinary tumor boards (MDTs). Discordance between clinical and pathologic TNM stage is particularly important for patients with locally advanced NSCLC (stage IIIA) because it may influence their chance of allocation to curative-intent treatment. We therefore aimed to study agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…In NSCLC, precise diagnosis and adequate staging are essential to ensure uniform allocation to the best treatment strategy, but these parameters may differ among MDTs. In 2020, Dutch investigators showed a high grade of variability in T and N staging and treatment recommendation in a series of 110 patients with stage IIIA NSCLC among MDTs in different hospitals [30]. Agreement on clinical staging and treatment recommendations was rated using Randolph's free-marginal multi-rater kappa as a chance-adjusted index.…”
Section: Stage III Nsclc: a Mtb Paradigmmentioning
confidence: 99%
“…In NSCLC, precise diagnosis and adequate staging are essential to ensure uniform allocation to the best treatment strategy, but these parameters may differ among MDTs. In 2020, Dutch investigators showed a high grade of variability in T and N staging and treatment recommendation in a series of 110 patients with stage IIIA NSCLC among MDTs in different hospitals [30]. Agreement on clinical staging and treatment recommendations was rated using Randolph's free-marginal multi-rater kappa as a chance-adjusted index.…”
Section: Stage III Nsclc: a Mtb Paradigmmentioning
confidence: 99%
“…A notable strength of our analysis is the access to all patient records and the written MDT deliberations for each patient. An important study limitation is the fact that treatment recommendation for stage III NSCLC may vary considerably between Dutch MDTs, 21 making our findings less representative for Dutch national practice. In addition, full capture of all eligible patients was ensured using both Netherlands Cancer Registry data and hospital records, but we cannot exclude the possibility that some cases of stage III NSCLC might have been missed, such as patients who may not have been staged appropriately or who were not registered in the Netherlands Cancer Registry or MDT notes.…”
Section: Discussionmentioning
confidence: 85%
“…With this in mind, it is reasonable to assume that outcomes reflect the composition and expertise of the treatment team. For example, a recent study showed considerable variation in clinical staging and treatment recommendation among multidisciplinary tumor boards (MTB), largely attributable to T-staging, in particular in patients with locally advanced lung cancer, which is the case for most SST patients [29]. The input of experienced and knowledgeable clinicians during MTB discussions is important, especially when deciding things like the feasibility and usefulness of an extensive operation after multi-modal induction treatment [30].…”
Section: Discussionmentioning
confidence: 99%